Targeting acetate kinase of Porphyromonas gingivalis: a computational approach to identifying novel inhibitors for endodontic infection treatment: Targeting acetate kinase of P. gingivalis - Boreak, Nezar; Jafari , Shatha Ahmad; Alotaibi, Huriyyah Meshal; Abbas, Thekra Saud Abdullah; Bokar, Abdullah Mohammed; Muaddi , Hajer Bader; Alshammakhy, Reem; Almughallis , Ghadeer Ahmed; Judayba, Musab Hassan Abdullah; Hakami, Essa Mohammed (Cellular and Molecular Biology, 2025)
This study explores a novel approach to treating endodontic infections by targeting the acetate kinase (Ack) enzyme of Porphyromonas gingivalis, a key pathogen in these infections. Using computational methods, we developed an apo receptor-based E-pharmacophore model of P. gingivalis Ack and screened the ZINC Lead-Like database containing over 1.8 million compounds. High-throughput virtual screening and molecular dynamics simulations identified ZINC001306857494 as a promising lead compound, demonstrating stable binding to the Ack active site with a binding free energy of -41.66 kcal/mol. The compound forms multiple hydrogen bonds with highly conserved residues, including Leu119, His180, and Arg241. Molecular dynamics simulations over 250 ns confirmed the stability of the protein-ligand complex, with sustained interactions throughout the simulation period. This study presents a potential new scaffold for developing Ack inhibitors, offering a promising avenue for treating endodontic infections caused by P. gingivalis.